Género, ciudadanía y cuidado: aportes al debate en América Latina - Gómez Urrutia, Verónica (El Colegio de México A.C., 2010)
This paper analyses some of the issues posed by carework from the perspective of its contribution to the maintenance and survival of political communities. Carework –which has been historically performed mainly by women- presupposes the sexual division of labour into “productive” and “reproductive”, and the exclusion of the later from the conditions that are considered as necessary to ensure society’s cohesion and welfare. The paper proposes arguments in favour of linking the concept of care (with its gendered implications) with the concept of citizenship, so as to conceptualise carework as part of the political duties of men and women towards their communities, but also as a right that can be guaranteed to anybody in situation of temporary or permanent vulnerability.